PROPHETIC LEADERSHIP MODEL: META-ANALYSIS AND SYSTEMIC REVIEW - Kurniawati, Eti; Tarihoran, Naf’an; Nugraha, Enung (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to analyze the prophetic leadership model through a meta-analysis and systematic review approach. Prophetic leadership is a model based on moral, ethical, and spiritual values that have proven effective in improving organizational performance and employee motivation and building a harmonious work culture. This study reviews previous research conducted between 2020–2024 to identify factors that influence the effectiveness of prophetic leadership in various sectors. The study results show that prophetic leadership positively impacts job satisfaction, employee engagement, and creating an organizational culture based on ethics and spirituality. However, challenges are still in implementing this model, especially in organizations with diverse cultural backgrounds. Therefore, a more adaptive implementation strategy is needed to apply prophetic leadership more widely in various organizational contexts. This study provides insights into prophetic leadership's role in sustainable organizational development.